Chromosomal diversification of diploid number, heterochromatin and rDNAs in two species of Phanaeus beetles (Scarabaeidae, Scarabaeinae) - Arcanjo,Amanda (2013)
The genus Phanaeus is included in the tribe Phanaeini, one of the most diverse tribes within the subfamily Scarabaeinae in terms of chromosomal characteristics. However, so far the species of this genus were not studied with differential cytogenetic techniques, limiting any inference of the probable mechanisms responsible for this diversity. In this work, several techniques were applied with the aim of cytogenetically characterizing two Phanaeus species. The karyotype found for Phanaeus (Notiophanaeus) chalcomelas was 2n = 12, neo-XY, and that of P. (N.) splendidulus was 2n = 20, Xy p, considered primitive for the family Scarabaeidae. The chromosomes of both species showed a high amount of constitutive heterochromatin (CH), with blocks rich in base pairs GC (CMA3+). Moreover, in P. (N.) chalcomelas the marks revealed by C-banding and fluorochrome staining were different in size, showing CH variability. Sites of 18S ribosomal DNA (rDNA) were identified in one autosomal pair of P. (N.) chalcomelas and in five autosomal pairs of P. (N.) splendidulus. On the other hand, only one autosomal pair exhibited 5S rDNA sequences in these species. The results suggest that the karyotype differentiation of the Phanaeus species studied here involved pericentric inversions and centric fusions, as well as mechanisms related to amplification and dispersion of CH and rDNA sequences.